Energy-aware production planning with renewable energy generation considering combined battery: And hydrogen-based energy storage systems - Gabriel Benedikt Thomas Adams (Junior Management Science (JUMS), 2025)
This study investigates the capacity of a developed production planning model to coordinate energy management within a hybrid energy system. The specific focus is on energy-intensive manufacturing firms utilizing renewable energy generation and energy storage. Unlike prior research in the field of energy-aware production planning, which revealed considerable cost saving potentials for the consideration of energy storage, this study considers a combined battery- and hydrogen-based energy storage with more realistic technology modeling. A formal mathematical model is developed as a mixed-integer linear program. Moreover, the cost saving potential of the combined energy storage system in energy-aware production planning is investigated based on numerical experiments. The experiments reveal that the implementation of the proposed planning approach saves significant costs compared to a baseline scenario. Up to 29.3 % cost saving potentials can be reached. In particular, the battery storage achieves significant energy cost savings while the hydrogen storage improves independence from fluctuating energy tariffs and availability of renewable energy. Possible model extensions are suggested to enhance the utilization of the proposed planning approach.
Keywords: 650; energy-aware production planning; energy storage systems; hydrogen; mixed-integer linear programming; renewable energy generation